2014
DOI: 10.1177/0961203314555538
|View full text |Cite
|
Sign up to set email alerts
|

Anti-N-methyl-D-aspartate receptor and anti-ribosomal-P autoantibodies contribute to cognitive dysfunction in systemic lupus erythematosus

Abstract: These results reveal an association of active disease together with specific circulating autoantibodies, such as anti-NMDAR and anti-P, with cognitive dysfunction in SLE patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 63 publications
1
33
0
Order By: Relevance
“…Numerous later studies corroborated such an association . Anti‐P autoantibodies have recently been shown to be involved, along with anti– N ‐methyl‐ d ‐aspartate receptor (anti‐NMDAR), in the cognitive impairment of SLE patients . In addition, passive‐transfer experiments in mice showed that anti‐P autoantibodies induced smell alterations , depression‐like manifestations , and memory impairment .…”
mentioning
confidence: 87%
“…Numerous later studies corroborated such an association . Anti‐P autoantibodies have recently been shown to be involved, along with anti– N ‐methyl‐ d ‐aspartate receptor (anti‐NMDAR), in the cognitive impairment of SLE patients . In addition, passive‐transfer experiments in mice showed that anti‐P autoantibodies induced smell alterations , depression‐like manifestations , and memory impairment .…”
mentioning
confidence: 87%
“…1) SLE and Sjögren’s syndrome : Besides purely neuropsychiatric forms of SLE, subtle to major cognitive alterations were demonstrated in up to 20% of SLE patients 129 . Cognitive clinical signs in SLE are accompanied with high titers of anti-N-methyl-D-aspartate receptor (NMDA; also named NR2 glutamate receptor) and/or anti-ribosomal antibodies 130, 131 .…”
Section: The Cns Is a Major Source Of Superautoantigensmentioning
confidence: 99%
“…Several antibodies are reported to be associated with cognitive dysfunction. Anti‐phospholipid antibodies, anti‐N‐methyl‐D‐aspartate (NMDA) receptor and anti‐ribosomal‐p autobodies in SLE and anti‐thyroid antibodies in Hashimoto's ensephalopathy have been reported . Moreover, antiganglioside antibodies may have a potential role in neurological manifestations of several diseases, such as neurodegenerative diseases, dementia, SLE, SS, mixed cryoglobulinemia and idiopathic systemic vasculitis .…”
Section: Introductionmentioning
confidence: 99%